Capturing the transition of historic urban landscapes using scores from Hanoi’s ancient quarter - Saori Kashihara; Chi Quynh Le (Journal of Asian Architecture and Building Engineering, 2025)
Asian cities are exposed to dynamic changes in their historic urban landscapes (HULs). However, the ways in which to quantify the degree of landscape change to guide spatial management have remained underexplored. Taking rapidly changing Hàng Buồm Street, Hanoi, Vietnam, as case study, we developed a numerical score for HULs to capture change tendencies. From onsite surveys, we defined the intensity and speed of change in trade and façades and identified vulnerable spots by mapping the scores for 131 units in 2015, 2017, and 2019. Our results showed that superficial façade changes happened regardless of the degree of trade change, and that the intense façade and trade changes happened around junctions with heavily touristified streets. We also found that aside from conventional tourism, newly emerging nighttime economies, wellness tourism, and multifunctional complexes had more intense façade changes. Based on these findings, we propose refining current management strategies by preparing stricter guidelines to control the aforementioned highly influential trades, establishing urban design project for old street to improve management of junctions especially with heavily touristified streets, and providing detailed examples of appropriate signboards that can easily be referenced by merchants and investors.